Identification of a strategy for disinvestment in the Italian National Health Service (NHS). (13th November 2019) - Cadeddu, C; Di Brino, E; Campisi, F; Meloni, A; Romeo, S; Montemagno, M; Cicchetti, A; Marchetti, M
Abstract: : The disinvestment of ineffective or inappropriate technologies or interventions with an inadequate value for money ratio is a growing priority in order to contribute to the objectives of maintaining high quality and appropriate care and allocation of resources that guarantee the sustainability of the National Health System (NHS).The possibility of reallocating resources from obsolete and no longer appropriate technologies, allows for recovered resources to be allocated to technological innovation and therefore to the overall sustainability of the system.In order to define criteria concerning disinvestment techniques of health technologies and strategies of obsolete technologies to be applied within the Italian reference framework, we started an ongoing research project. A systematic review of the scientific literature of the last 10 years was carried out on 5 different databases with the purpose of analyzing the international disinvestment experiences of health technologies using the Health Technology Assessment (HTA) method and focusing on orthopedic prosthesis procedure and cardiac stenting procedure.By means of National Dataset of the Italian National Institute of Health, real consumption and estimated consumption have been identified, using the Italian NHS perspective. The preliminary systematic review retrieved a total of 548 records. Nine results were finally included. In the development of disinvestment strategies, particular attention must be paid to the identification of an integrated model between the different levels of the NHS (national, regional, local). In Italy there are no prior example of broad and complex disinvestment experiences using HTA methodologies. Effective disinvestment strategies require a systematic approach coordinated by a national body and implemented at regional level, to be extended to cascade to the organization and provision of services and services by health companies, and required to actively involve health professionals and citizens. Key messages: Identifying effective strategies for disinvestment of health technologies is crucial, considering continuous health innovation and improvement and development opportunities. HTA methodologies, such as reassessment, could support disinvestment processes and represent a systematic and objective approach to be implemented and used at different levels of Italian NHS.